The complex impact of artificial intelligence on physician-patient connection - Jóna, György (Magyar Gerontológia, 2024)
The doctor-patient relationship can be regarded as an integral segment of social support that possesses relevant therapeutic impact. Recently, the doctor-patient relationship has been reshaped basically that has been accelerated by health digitalization.